Oxidative stress and platelet activation in subjects with moderate hyperhomocysteinaemia due to MTHFR 677 C→T polymorphism - Dragani, Alfredo; Falco, Angela; Santilli, Francesca; Basili, Stefania; Rolandi, Giancarlo; Cerasa, Loredana; Lattanzio, Stefano; Ciabattoni, Giovanni; Patrono, Carlo; Davì, Giovanni (Thrombosis and Haemostasis, 2012)
The methylenetetrahydrofolate reductase (MTHFR) 677 C→T polymorphism may be associated with elevated total homocysteine (tHcy) levels, an independent risk factor for cardiovascular disease. It was the study objective to evaluate in vivo lipid peroxidation and platelet activation in carriers of the MTHFR 677 C→T polymorphism and in non-carriers, in relation to tHcy and folate levels. A cross-sectional comparison of urinary 8-iso-prostaglandin (PG)F2α and 11-dehydro-thromboxane (TX)B2 (markers of in vivo lipid peroxidation and platelet activation, respectively) was performed in 100 carriers and 100 non-carriers of the polymorphism. A methionine-loading test and folic acid supplementation were performed to investigate the causal relationship of the observed associations. Urinary 8-iso-PGF2α and 11-dehydro-TXB2 were higher in carriers with hyperhomocysteinaemia than in those without hyperhomocysteinaemia (p<0.0001). Hyperhomocysteinaemic carriers had lower folate levels (p=0.0006), higher urinary 8-iso-PGF2α (p<0.0001) and 11-dehydro-TXB2 (p<0.0001) than hyperhomocysteinaemic non-carriers. On multiple regression analysis, high tHcy (p<0.0001), low folate (p<0.04) and MTHFR 677 C→T polymorphism (p<0.001) independently predicted high rates of 8-iso-PGF2α excretion. Methionine loading increased plasma tHcy (p=0.002), and both urinary prostanoid metabolites (p=0.002). Folic acid supplementation was associated with decreased urinary 8-iso-PGF2α and 11-dehydro-TXB2 excretion (p<0.0003) in the hyperhomocysteinaemic group, but not in the control group, with substantial inter-individual variability related to baseline tHcy level and the extent of its reduction. In conclusion, hyperhomocysteinaemia due to the MTHFR 677 C→T polymorphism is associated with enhanced in vivo lipid peroxidation and platelet activation that are reversible, at least in part, following folic acid supplementation. An integrated biomarker approach may help identifying appropriate candidates for effective folate supplementation.
Keywords: Hyperhomocysteinaemia; MTHFR 677 C→T polymorphism; oxidative stress; platelet activation; folate supplementation